The seahorse (Hippocampus comes L.) extract ameliorates sperm qualities, testosterone level, and serum biochemistry in rats induced by depo medroxyprogesterone acetate (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The percentage of infertility cases in this world is about 50%. Seahorses (Hippocampus spp.) are widely used in traditional medicine. Several studies suggest that seahorses have ethno pharmacological characteristics, such as fertility, antioxidants, and antifatigue. The purpose of this study was to determine whether seahorse extract (SE) (Hippocampus comes L.) has an effect on fertility and serum biochemistry in rats induced by depo medroxyprogesterone acetate (DMPA). Materials and Methods: All animals were induced with 1.25 mg/kg BW of DMPA. Animals were grouped into five groups: namely aquadest, 1% CMC, and SE doses of 150, 225, and 300 mg/kg BW. The rats were gavage every morning from week 7 until 18. At the end of our study, semen from the vas deferens and blood from the heart were analyzed. We analyzed with a one-way analysis of variance and Bonferroni’s post hoc tests (α 95%). Results: The concentration of spermatozoa had a significant difference in dose of 150 mg/kg BW compared to other groups (p = 0.04). In contrast, the motility (p = 0.012) and viability of spermatozoa (p = 0.007) were highly significant differences (p < 0.05 and p < 0.01) at 300 mg/kg BW. Testosterone levels were not significantly (p = 0.162; p > 0.05), but tended to increase at 300 mg/ kg BW (11.01%). Nevertheless, serum biochemistry was insignificant (p > 0.05) in all groups. Conclusion: SE (Hippocampus comes L.) ameliorates fertility and serum biochemistry in rats induced by DMPA.J. Adv. Vet. Anim. Res., 10(1): 126–131, March 2023http://doi.org/10.5455/javar.2023.j661